Observations of forest specialists in Northern Finland on the berry yield capacity of forests and swamps - Sepponen, Pentti (Silva Fennica, 1984)
A survey was carried out among forest foremen and forest technicians to record their observations on the value of various swamp and forest types as producers of berries and on the effect of drainage of peatlands upon the berry yields. Comparative agreement existed on the best blueberry ( L.) forest types and on the best lingonberry ( L.) forest types of rather dry upland sites. pine swamps or bogs were considered best for the most part as regards the yield of cloudberry (R L.). The replies showed rather great dispersion.Vaccinium myrtillusVaccinium vitis-idaeaFuscumfuscumubus chamaemorus